ANALYZING SEGMENTAL FEATURES: THE ROLE OF CONSONANTS AND VOWELS IN PHONOLOGICAL PATTERNS - Yani Lubis; Dinda Sundana; Rizki Tiara Ayunda; Alya Fadhillah Dalimunthe; Irpi Octia Pebrianti (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
The distinguishing features are vowels, consonants, and consonants where the vowel is pronounced with the tongue or lips, and the opposite form of the mouth is a sound that stops or stops in the airflow, or sound or sounds produced by some type of shutter. However, Avery and Ehrlich report a narrowing of the mouth that prevents active airflow..This study used a survey method. According to Kirk and Miller, knowledge comes from quality, not quantity.Phonology deals with this type of etymological discussion. Phonetics is the art of describing speech sounds. Phonology is the study of how speech sounds shape and structure human language. Language deals with the structure and pattern of speech sounds.